2005
DOI: 10.1016/j.specom.2005.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Vowel perception: Effects of non-native language vs. non-native dialect

Abstract: Three groups of listeners identified the vowel in CV and VC syllables produced by an American English talker. The listeners were (a) native speakers of American English, (b) native speakers of Australian English (different dialect), and (c) native speakers of Dutch (different language). The syllables were embedded in multispeaker babble at three signal-tonoise ratios (0 dB, 8 dB, and 16 dB). The identification performance of native listeners was significantly better than that of listeners with another language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…Cross-dialect difficulties in phoneme perception, however, seem to be of lesser magnitude than cross-language difficulties. Cutler et al (2005) asked Australian, American, and Dutch listeners to identify American English vowels in meaningless CV and VC syllables, and found that overall, the Australian and American listeners performed equally well, although the Australians were systematically affected by the tendency to greater vowel tenseness in their native dialect (reporting, for example, /O/ as /A/ more than vice versa). The Dutch listeners' overall performance, however, was significantly worse, suggesting that language differences have greater consequences than dialect differences for the perception of phonemes.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-dialect difficulties in phoneme perception, however, seem to be of lesser magnitude than cross-language difficulties. Cutler et al (2005) asked Australian, American, and Dutch listeners to identify American English vowels in meaningless CV and VC syllables, and found that overall, the Australian and American listeners performed equally well, although the Australians were systematically affected by the tendency to greater vowel tenseness in their native dialect (reporting, for example, /O/ as /A/ more than vice versa). The Dutch listeners' overall performance, however, was significantly worse, suggesting that language differences have greater consequences than dialect differences for the perception of phonemes.…”
Section: Introductionmentioning
confidence: 99%
“…This native listening advantage is at least partially due to a more efficient use of higher level information, to compensate for the loss of intelligibility at lower levels of processing. Cutler and colleagues, e.g., found no difference between native and non-native listen ers' perception of phonemes in noise (Cutler et al, 2004(Cutler et al, , 2005 unless there was even the smallest amount of predict ability in the form of a constant noise lead duration that native listeners could benefit from (Cutler et al, 2008). Fur ther, for native but not for non-native listeners, noise hin dered the recognition of words less when they were preceded by a semantically related word than when they were preceded by a semantically unrelated word (Golestani et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We predict that Western speakers will show difficulties distinguishing the /s̺ /-/s̻ / contrast at a low, acoustic-phonetic level, given that this distinction is not part of their native inventory. However, based on what similar studies show (Cutler et al, 2005;Dufour et al, 2007), Western speakers may have some sensitivity to the apical-laminal distinction due to its presence in their linguistic environment (TV, radio, school, interactions with Standard speakers, etc. ), where Standard Basque -and therefore, the /s̺ /-/s̻ / contrast -is often used.…”
Section: Experiments 1: Axb Discrimination Taskmentioning
confidence: 99%